Benchmarking of T cell receptor repertoire profiling methods reveals large systematic biases - Barennes, Pierre; Quiniou, Valentin; Shugay, Mikhail; Egorov, Evgeniy S; Davydov, Alexey N; Chudakov, Dmitriy M; Uddin, Imran; Ismail, Mazlina; Oakes, Theres; Chain, Benny; Eugster, Anne; Kashofer, Karl; et al. (Nature biotechnology, 2021)
Monitoring the T cell receptor (TCR) repertoire in health and disease can provide key insights into adaptive immune responses, but the accuracy of current TCR sequencing (TCRseq) methods is unclear. In this study, we systematically compared the results of nine commercial and academic TCRseq methods, including six rapid amplification of complementary DNA ends (RACE)-polymerase chain reaction (PCR) and three multiplex-PCR approaches, when applied to the same T cell sample. We found marked differences in accuracy and intra- and inter-method reproducibility for T cell receptor α (TRA) and T cell receptor β (TRB) TCR chains. Most methods showed a lower ability to capture TRA than TRB diversity. Low RNA input generated non-representative repertoires. Results from the 5' RACE-PCR methods were consistent among themselves but differed from the RNA-based multiplex-PCR results. Using an in silico meta-repertoire generated from 108 replicates, we found that one genomic DNA-based method and two non-unique molecular identifier (UMI) RNA-based methods were more sensitive than UMI methods in detecting rare clonotypes, despite the better clonotype quantification accuracy of the latter.
Keywords: Jurkat Cells; Male; High-Throughput Nucleotide Sequencing; receptory antigenů T-buněk alfa-beta; Computer Simulation; Jurkat buňky; zkreslení výsledků (epidemiologie); Adult; dospělí; mužské pohlaví; reprodukovatelnost výsledků; Reproducibility of Results; receptory antigenů T-buněk; Receptors, Antigen, T-Cell; lidé; Humans; vysoce účinné nukleotidové sekvenování; Bias; počítačová simulace; lidé středního věku; Receptors, Antigen, T-Cell, alpha-beta; Middle Aged